Safety and efficacy of icatibant self-administration for acute hereditary angioedema - Boccon-Gibod, I (Blackwell Publishing Ltd, 2012)
We evaluated the efficacy and safety of icatibant self-administration in 15 patients with hereditary angioedema (HAE) types I or III, for 55 acute attacks (mostly severe or very severe). Icatibant self-administration was generally effective: first symptom improvement occurred in 5 min–2 h (HAE type I; n = 17) and 8 min–1 h (HAE type III; n = 9) for abdominal attacks and 5–30 min (HAE type I; n = 4) and 10 min–12 h (HAE type III; n = 6) for laryngeal attacks. Complete symptom resolution occurred in 15 min–19 h (HAE type I; n = 8) and 15 min–48 h (HAE type III; n = 9) for abdominal attacks and 5–48 h (HAE type I; n = 3) and 8–48 h (HAE type III; n = 5) for laryngeal attacks. No patient required emergency hospitalization. The only adverse events were mild, spontaneously resolving injection site reactions. Patients reported that carrying icatibant with them gave them greater confidence in managing their condition.